Answer:
y=1/3x+5/3
Step-by-step explanation:
y=1/3x+b
1=1/3(-2)+b (plug in ya points)
1=-2/3+b
5/3=b
y=1/3x+5/3
Answer:
(-2, 5)
Step-by-step explanation:
A reflection across the origin turns the point (a, b) into (-a, -b).
Put -4 in place of x
-4 to the second power is 16 so it would be 16-(-12)= 28
Answer:
Step-by-step explanation:
g(x)= -x-1 or g(x) = x+1
if g(x) = -x-1
-x-1=2x+4
-x=2x+5
-x/2=x+5
-x/2 -x=5
-x/2-2x/2=5
-x-2x=5
-3x=5
x=5/-3
if g(x) = x+1
x+1=2x+4
x=2x+3
x/2=x+3
x/2-x=3
x/2-2x/2=3
x-2x=3
-x=3
x=3